2008
DOI: 10.1002/pmic.200701141
|View full text |Cite
|
Sign up to set email alerts
|

Towards identifying Brassica proteins involved in mediating resistance to Leptosphaeria maculans: A proteomics‐based approach

Abstract: To better understand the pathogen-stress response of Brassica species against the ubiquitous hemi-biotroph fungus Leptosphaeria maculans, we conducted a comparative proteomic analysis between blackleg-susceptible Brassica napus and blackleg-resistant Brassica carinata following pathogen inoculation. We examined temporal changes (6, 12, 24, 48 and 72 h) in protein profiles of both species subjected to pathogen-challenge using two-dimensional gel electrophoresis. A total of 64 proteins were found to be significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…However, there is no such study in which a proteomics approach has been deployed in the incompatible interaction of B. napus-S. sclerotiorum pathosystem, even though the protein profile of a compatible interaction of this pathosystem [25] and of fungal mycelia of S. sclerotiorum and its secretome have already been explored [26]. Proteomic analysis is now considered to be a powerful tool to study plant-pathogen interaction by which differentially expressed proteins induced in response to the pathogen challenge can be identified [27], [28]. This technique is a valuable complement for genomic approaches for investigations into plant-pathogen interactions at the molecular level, particularly as it provides a continuity between genome sequence information with the protein profile, which in turn indicates possible biochemical cellular pathways involved [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no such study in which a proteomics approach has been deployed in the incompatible interaction of B. napus-S. sclerotiorum pathosystem, even though the protein profile of a compatible interaction of this pathosystem [25] and of fungal mycelia of S. sclerotiorum and its secretome have already been explored [26]. Proteomic analysis is now considered to be a powerful tool to study plant-pathogen interaction by which differentially expressed proteins induced in response to the pathogen challenge can be identified [27], [28]. This technique is a valuable complement for genomic approaches for investigations into plant-pathogen interactions at the molecular level, particularly as it provides a continuity between genome sequence information with the protein profile, which in turn indicates possible biochemical cellular pathways involved [29].…”
Section: Introductionmentioning
confidence: 99%
“…carinata has been recently introduced instead of the traditional winter rapes (Brassica juncea L. Czern. and Brassica napus L.) because of its higher tolerance to abiotic and biotic stresses (Sharma et al, 2008;Canam et al, 2013) and its good productivity under low-input conditions. Even more interest arose on its oil rich in erucic and linolenic acid (Velasco et al, 2003) and its possible uses in industrial applications (Atabani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They also respond to photosynthetic signals, such as the acceptor availability at photosystem II and abscisic acid, and ROS signals in the plant cell [46]. Previous studies showed that peroxiredoxins are regulated in plants growing under biotic and abiotic environments [47,48]. In line with these results, we found that 2-Cys Prx BAS1 (spot R1) was upregulated in both male and female P. cathayana cuttings exposed to 4-wk Mn stress ( Table 2 and Supporting Information S1 and S2 and Figs.…”
Section: Differently Expressed Stress and Defense Proteinsmentioning
confidence: 88%